Strategi Pengembangan Identitas Visual Profesional untuk UMKM melalui Jasa Pembuatan Logo - Ahmad Jj Beniko; Hafidh Sandy Mahardika; Reiza Mahendra Abimanyu; Matthew Ieuan Constantino; Muhammad Yodho Alif; Rico Syahputra; Surya Aji (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This Community Service focuses on logo creation services for MSMEs, presented as a solution to help Micro, Small, and Medium Enterprises create a professional and attractive visual identity for customers. This service not only alleviates the time burden experienced by often busy MSME actors but also contributes to increasing the popularity and brand recognition of MSMEs through attractive logo designs. With a better logo, MSMEs can develop their brand more effectively, attract more customers, and compete in this increasingly competitive digital market.